2022
DOI: 10.21203/rs.3.rs-2365752/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermodynamic origin of nonvolatility in resistive switching

Abstract: Electronic switches based on the migration of high-density point defects, or memristors, are poised to revolutionize post-digital electronics. Despite significant research, key mechanisms for filament formation and oxygen transport remain unresolved, thus hindering our ability to predict and design crucial device properties. For example, predicted retention times based on current models can be 10 orders of magnitude lower than ones experimentally realized. Here, using electrical measurements, chemical spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Unfortunately, this descriptor does not describe the ionic conductivity in amorphous materials. In this work and our other work, 10 we found that oxygen-deficient metal suboxides have much lower ionic conductivity than near-stoichiometric metal oxides. Instead, amorphous hafnium oxide made through atomic layer deposition has much lower oxygen tracer diffusivity than ones made through reactive sputtering.…”
supporting
confidence: 70%
“…Unfortunately, this descriptor does not describe the ionic conductivity in amorphous materials. In this work and our other work, 10 we found that oxygen-deficient metal suboxides have much lower ionic conductivity than near-stoichiometric metal oxides. Instead, amorphous hafnium oxide made through atomic layer deposition has much lower oxygen tracer diffusivity than ones made through reactive sputtering.…”
supporting
confidence: 70%
“…It was recently shown that oxygen may undergo ''uphill'' diffusion against the concentration gradient because of spinodal decomposition. 26 However, these devices would fail from the high-resistance to the low-resistance state. Our results show device failure from the low-resistance to the high-resistance state (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we investigate oxygen tracer diffusion in amorphous HfO 2 thin films deposited by sputtering and by atomic layer deposition. To study oxygen tracer diffusion in sputtered HfO 2 , we deposited tri-layer samples 26 comprised of an 18 O-enriched HfO 2 layer sandwiched between natural-abundance oxygen HfO 2 oxide layers as shown in Fig. 2a; all three layers are nominally identical chemically (HfO 2 ).…”
Section: Oxygen Tracer Diffusion In Amorphous Hfomentioning
confidence: 99%